Mapping sex differences in the effects of protein and carbohydrates on lifespan and reproduction in Drosophila melanogaster: is measuring nutrient intake essential? - Matthew R. Carey; C. Ruth Archer; James Rapkin; Meaghan Castledine; Kim Jensen; Clarissa M. House; David J. Hosken; John Hunt (Biogerontology, 2022)
Understanding how diet affects reproduction and survival is a central aim in evolutionary biology. Although this relationship is likely to differ between the sexes, we lack data relating diet to male reproductive traits. One exception to this general pattern is Drosophila melanogaster, where male dietary intake was quantified using the CA pillary FE eder (CAFE) method. However, CAFE feeding reduces D. melanogaster survival and reproduction, so may distort diet-fitness outcomes. Here, we use the Geometric Framework of Nutrition to create nutrient landscapes that map sex-specific relationships between protein, carbohydrate, lifespan and reproduction in D. melanogaster. Rather than creating landscapes with consumption data, we map traits onto the nutrient composition of forty agar-based diets, generating broad coverage of nutrient space. We find that male and female lifespan was maximised on low protein, high carbohydrate blends (~ 1 P :15.9 C ). This nutrient ratio also maximised male reproductive rates, but females required more protein to maximise daily fecundity (1 P :1.22 C ). These results are consistent with CAFE assay outcomes. However, the approach employed here improved female fitness relative to CAFE assays, while effects of agar versus CAFE feeding on male fitness traits depended on the nutrient composition of experimental diets. We suggest that informative nutrient landscapes can be made without measuring individual nutrient intake and that in many cases, this may be preferable to using the CAFE approach. The most appropriate method will depend on the question and species being studied, but the approach adopted here has the advantage of creating nutritional landscapes when dietary intake is hard to quantify.